Long-term coastline evolution of Figueira da Foz - Nazaré sector (Portugal) - Nave, Silvia (2022)
ABSTRACT: ome sectors of the west Portuguese coast are particularly endangered by erosion and flooding. Regional to local scale information, on coastline evolutionary trend, is particularly valuable in sectors that includes areas with relevant erosion. A continuous, high-resolution, dataset on coastal evolution, from 1947 and 2015, between Figueira da Foz and Nazaré, was achieved within the Programme “Geological and Coastal Hazard Mapping at a 1:3000 resolution scale” at the National Laboratory of Energy and Geology (LNEG). This work, due to the detailed scale of analysis in a wide geographic context, allows to have both, a general overview of the coastal evolution and, at the same time, when zooming in up to 1:3000 scale, to observe the local behaviour and to quantify the occurred changes. Also, the well time-spaced aerial photograph dataset allows to compare the resultant coastline movement between the oldest and the youngest coastline (NSM index), with the total coastline oscillation (SCE index), bringing new insights on the coastline stability at a local scale. The evolution trend shows an overall erosional behaviour, if considering the entire sector. Erosion occurs predominantly in the north, as the south shows more stability and progradation. Quantification of the land-lost and land-gain due to the coastline shift in a 68-year period shows that 1 164 888 m2 of land were lost along 30 470 m of the coastal fringe, and 462 330 m2 were gained along an extension of 21 010 m.